Astrocytic Interleukin-15 Reduces Pathology of Neuromyelitis Optica in Mice - Li, Zhiguo; Han, Jinrui; Ren, Honglei; Ma, Cun-Gen; Shi, Fu-Dong; Liu, Qiang; Li, Minshu (Frontiers in Immunology, 2018)
Astrocyte loss induced by NMO-IgG and complement-dependent cytotoxicity (CDC) is the hallmark of NMO pathology. The survival of astrocytes are thought to reflect astrocyte exposure to environmental factors in the CNS and the response of astrocytes to these factors. However, still unclear are how astrocytes respond to NMO-IgG and CDC, and what CNS environmental factors may impact the survival of astrocytes. In a murine model of NMO induced by intracerebral injection of NMO-IgG and human complement, we found dramatic upregulation of IL-15 in astrocytes. To study the role of astrocytic IL-15 in NMO, we generated a transgenic mouse line with targeted expression of IL-15 in astrocytes, in which the expression of IL-15 is controlled by a glial fibrillary acidic protein (GFAP) promoter. We showed that astrocyte-targeted expression of IL-15 attenuates astrocytes and aquaporin 4 loss in the brain. Reduced BBB leakage and immune cells infiltration are also found in the lesion of IL-15tg mice subjected to NMO induction. In vitro data indicates that IL-15tg astrocytes are less susceptible to NMO-IgG-mediated CDC when compared to their WT littermates. Importantly, IL-15 enhances the ability of astrocyte to resistant to cytotoxicity and cell death via NF-кB signaling pathway. Our findings suggest that IL-15 reduces astrocyte loss and NMO pathology.